Four Variations Detected in 3 Genes Related to Thrombophilia by Multiplex ARMS – PCR - Thi Quynh Trang, Tran; Thuy Ngan, Nguyen; Thi Than, Nguyen; The Tung, Pham; Lan, Vo Thi Thuong (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 4, 2021)
Thrombophilia is a condition that may cause venous obstruction, leading to serious illnesses such as stroke, respiratory failure, and even death. This condition is hereditary or related to the immune system. Inherited thrombophilia is screened by analysing genetic variants (allele). In this study, we analyse 4 variations in 3 genes, which occur at high variable frequency, namely Methytetrahydrofolate Reductase (MTHFR C677T , MTHFR A1298C ) , Factor V Leiden (FVL C1691T ) and Plasminogen Activator Inhibitor 1 (PAI-1 5G/4G ), using allele-specific polymerase chain reaction (ARMS-PCR). The primers were designed using FastPCR program and PCR conditions were optimized to identify 8 alleles of 4 variants through 3 multiplex ARMS - PCR reactions. The accuracy of the ARMS - PCR results was confirmed by Sanger sequencing and the real time PCR commercial kit (SNP). Mastering the allele specific PCR technique contributes to the survey of genetic variations in the Vietnamese population in order to screen and treat thrombophilia-related diseases. Keywords Thrombophilia, allele-specific polymerase chain reaction (ARMS-PCR), variants MTHFR C677T, MTHFR A1298C, FVL C1691T, PAI-1 4G/5G. References [1] A. Dautaj, G. Krasi, V. Bushati et al., Hereditary Thrombophilia, Acta Biomedica, Vol. 90, No. 10S, 2019, pp. 44-46, https://doi.org/10.23750/abm.v90i10-S.8758. [2] M. G. Beckman, W. C. Hooper, S. E. Critchley, T. L. Ortel, Venous Thromboembolism: A Public Health Concern, American Journal of Preventive Medicine, Vol. 38, No. 4S, 2010, pp. S495-S501, https://doi.org/10.1016/j.amepre.2009.12.017. [3] G. E. Raskob, R. Silverstein, D. W. Bratzler et al., Surveillance for Deep Vein Thrombosis and Pulmonary Embolism: Recommendations from A National Workshop, American Journal Preventive Medicine, Vol. 38, No. 4S, 2010, pp. S502-S509, https://doi.org/10.1016/j.amepre.2010.01.010. [4] J. A. Heit, M. D. Silverstein, D. N. Mohr et al., The Epidemiology of Venous Thromboembolism in the Community, Thrombosis and Haemostasis, Vol. 86, No. 1, 2001, pp. 452-463, https://doi.org/10.1055/s-0037-1616243. [5] M. Cushman, A. W. Tsai, R. H. White et al., Deep Vein Thrombosis and Pulmonary Embolism in Two Cohorts: The Longitudinal Investigation of Thromboembolism Etiology, The American Journal of Medicine, Vol. 117, No. 1, 2004, pp. 19-25, https://doi.org/10.1016/j.amjmed.2004.01.018. [6] J. A. Heit, The Epidemiology of Venous Thromboembolism in the Community: Implications for Prevention and Management, Journal of Thrombosis and Thrombolysis, Vol. 21, No. 1, 2006, pp. 23-29, https://doi.org/10.1007/s11239-006-5572-y. [7] R. H. White, The Epidemiology of Venous Thromboembolism, Circulation, Vol. 107, No. 23 S1, 2003, pp. I4-I8, https://doi.org/10.1161/01.cir. 0000078468.11849.66. [8] A. Wahed, A. Dasgupta, Thrombophilias and Their Detection, Hematology and Coagulation: A Comprehensive Review for Board Preparation, Certification and Clinical Practice, Elsevier, United States of America, 2015, pp. 263-275. [9] SNP Biotechnology, SNP Detection Real-Time PCR Kits, http://www.snp.com.tr/EN,37/snp-detection-real-time-pcr-kits.html/, 2021 (accessed on: May 1st, 2021). [10] V. S. Le, K. T. Tran, H. T. P. Bui et al., A Vietnamese Human Genetic Variation Database, Human Mutation, Vol. 40, No. 10, 2019, pp. 1664-1675, https://doi.org/10.1002/humu.23835. [11] dbSNP – NCBI, Reference SNP (rs) Report (rs6025, rs1799762), https://www.ncbi.nlm.nih.gov/snp/,02021 2021 (accessed on: May 1st, 2021). [12] D. C. Rees, M. Cox, J. B. Clegg, World Distribution of Factor V Leiden, The Lancet, Vol. 346, No. 8983, 1995, pp. 1133-1134, https://doi.org/10.1016/s0140-6736(95)91803-5. A. Fateh, M. Aghasadeghi, S. D. Siadat et al., Comparison of Three Different Methods for Detection of IL28 rs12979860 Polymorphisms as A Predictor of Treatment Outcome in Patients with Hepatitis C Virus, Osong Public Health and Research Perspectives, Vol. 7, No. 2, 2016, pp. 83-89, https://doi.org/10.1016/j.phrp.2015.11.004. [13] T. Huang, J. Zhuge, W. W. Zhang, Sensitive Detection of BRAF V600E Mutation by Amplification Refractory Mutation System (ARMS)-PCR, Biomarker Research, Vol. 1, No. 3, 2013, https://doi.org/10.1186/2050-7771-1-3. [14] R. F. V. Medrano, C. A. D. Oliveira, Guidelines for the Tetra-primer ARMS-PCR Technique Development, Molecular Biotechnology, Vol. 56, 2014, pp. 599-608, https://doi.org/10.1007/s12033-014-9734-4. [15] C. Runcharoen, K. Fukunaga, I. Sensorn et al., Prevalence of Pharmacogenomic Variants in 100 Pharmacogenes Among Southeast Asian Populations under Tarmacogenomics Research Network (SEAPharm), Human Genome Variation, Vol. 8, No. 7, 2021, https://doi.org/10.1038/s41439-021-00135-z.